Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar IPAS Materi Kearifan Lokal Peserta Didik Kelas IV SDN Panggreh 2 Jabon Sidoarjo - Ilma Nasukha; Farida Istianah; Rica Istiqfarin Al Isa (Departement of Mathematics Education, 2023)
The research was conducted to analyze the application of the PBL learning model in improving problem solving skills and motivation in local wisdom material for fourth grade students at SDN Panggreh 2 Sidoarjo Regency in the 2022/2023 academic year. In this classroom action research consists of two cycles with the stages of planning, action, observation, and reflection. The subjects in the study were teachers and fourth grade students at SDN Panggreh 2 Jabon Sidoarjo totaling 28 students with details of 11 students being boys and 17 students being girls. The use of data collection techniques consists of observation techniques, learning achievement tests, and field notes when learning activities take place. There was an increase from Cycle I to Cycle II in the activities of teachers, students, and students' science learning outcomes with the percentage results being an increase when viewed from the percentage of classical learning completeness results in cycle I which was initially 67.8% with an average score of 66, 85 increased in the results of the implementation of cycle II to 92.85% with an average value of 81.85. Based on these result data by applying the Problem Based Learning (PBL) model of local wisdom material can improve the mathematics learning outcomes of fourth grade students at SDN Panggreh 2 Jabon Sidoarjo and provide learning conditions that make students feel safe, comfortable and fun and motivate students to be involved actively in learning activities.